2014
DOI: 10.14719/pst.2014.1.3.39
|View full text |Cite
|
Sign up to set email alerts
|

Anti-acne activity of Garcinia mangostana L.: A review

Abstract: Garcinia mangostana L. or mangosteen of the Clusiaceae has traditionally been employed as medicinal drugs for decades. A plethora of compounds are responsible for a wide range of medicinal properties and biological activities. The ethanol extract of the mangosteen rind has been found to be anti-inflammatory, antioxidant and anti-acne-causing bacteria. Many research studies have confirmed its potency, with the ethanol extract of the rind being able to inhibit pro-inflammatory cytokines (TNF-α) at relatively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…tinea pedis, in Australia was documented in a number of clinical studies (Tong et al, 1992;Martin and Ernst, 2004). Local usage of M. alternifolia against acne vulgaris was mentioned in Thai traditional medicine (Khumsupan and Gritsanapan, 2014), while the leaves of M. alternifolia and M. leucadendron have long been used for traditional therapy of psoriasis in South America (Amenta et al, 2000).…”
Section: The Genus Melaleuca In Traditional Medicinementioning
confidence: 99%
“…tinea pedis, in Australia was documented in a number of clinical studies (Tong et al, 1992;Martin and Ernst, 2004). Local usage of M. alternifolia against acne vulgaris was mentioned in Thai traditional medicine (Khumsupan and Gritsanapan, 2014), while the leaves of M. alternifolia and M. leucadendron have long been used for traditional therapy of psoriasis in South America (Amenta et al, 2000).…”
Section: The Genus Melaleuca In Traditional Medicinementioning
confidence: 99%
“…The small intestine is able to absorb far in excess of the body's requirements and as such, large portions of this organ can be removed without deleterious effects. However, changes in absorption and secretion homeostasis can rapidly lead to diarrhea, dehydration, electrolyte disturbance, and malnutrition [3].…”
Section: Introductionmentioning
confidence: 99%
“…AM is a major constituent of the pericarp of mangosteen fruit, and it shows promising antibacterial activity against P. acnes and S. aureus [11,12]. AM has also been found to possess antiinflammatory and antioxidant properties [13]. Reassuringly, a study by Larson et al (2010) investigated the toxicity of AM against young rats and found that it did not demonstrate any adverse effects, even at a high doses of 80 mg/kg [14].…”
Section: Introductionmentioning
confidence: 99%